Can machine learning models predict soil moisture evaporation rates? An investigation via novel feature selection techniques and model comparisons - Priyanka, Priyanka; Kumar, Praveen; Panda, Sucheta; Thakur, Tejinder; Uday, K. V.; Dutt, Varun (Frontiers in Earth Science, 2024)
Extreme weather events and global climate change have exacerbated the problem of evaporation rates. Thus, accurately predicting soil moisture evaporation rates affecting soil cracking becomes crucial. However, less is known about how novel feature engineering techniques and machine-learning predictions may account for estimating the soil moisture evaporation rate. This research focuses on predicting the evaporation rate of soil using machine learning (ML) models. The dataset comprised twenty-one ground-based parameters, including temperature, humidity, and soil-related features, used as features to predict evaporation potential. To tackle the high number of features and potential uncorrelated features, a novel guided backpropagation-based feature selection technique was developed to rank the most relevant features. The top-10 features, highly correlated with evaporation rate, were selected for ML model input, alongside the top-5 and all features. Several ML models, including multiple regression (MR), K-nearest neighbor (KNN), multilayer perceptron (MLP), sequential minimal optimization regression (SMOreg), random forest (RF), and a novel K-Nearest Oracles (KNORA) ensemble, were constructed for the purpose of forecasting the evaporation rate. The average error of these 1 Priyanka et al.models was assessed using the root-mean-squared error (RMSE). Experimental results showed that the KNORA ensemble model performed the best, achieving a 7.54 mg/hr RMSE in testing with the top-10 features. MLP was followed closely by a 25.1 mg/hr RMSE in the same testing. An empirical model using all features showed a higher RMSE of 1319.1 mg/hr, indicating the superiority of the ML models for accurate evaporation rate predictions. We highlight the implications of our results for climate-induced soil cracking in the real world.